2015
DOI: 10.1007/s11664-015-3867-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Copper Oxide Nanoparticles Fabricated by the Sol–Gel Method

Abstract: Copper oxide nanoparticles were successfully prepared by a sol-gel technique. An aqueous solution of copper nitrate Cu(NO 3 ) 2 and acetic acid was used as precursor. On addition of sodium hydroxide (NaOH) a precipitate of copper oxide was immediately formed. The copper oxide nanoparticles were characterized by use of x-ray diffractometry (XRD), thermogravimetric analysis (TGA), differential thermal analysis, differential scanning calorimetry, Fourier-transform infrared spectroscopy (FTIR), vibrating sample ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(40 citation statements)
references
References 29 publications
(27 reference statements)
2
34
0
Order By: Relevance
“…Figure 4 shows the spectra of the organoclay/Cu hybrid mate- as observed previously by Hadj-Hamou et al [41]. Sharp peak at 3600 cm ; a band at 624 cm −1 was attributed to some other form of Cu nanoparticles as observed in the XRD spectra [42].…”
Section: Ftir Studiessupporting
confidence: 60%
“…Figure 4 shows the spectra of the organoclay/Cu hybrid mate- as observed previously by Hadj-Hamou et al [41]. Sharp peak at 3600 cm ; a band at 624 cm −1 was attributed to some other form of Cu nanoparticles as observed in the XRD spectra [42].…”
Section: Ftir Studiessupporting
confidence: 60%
“…Diffraction peaks at 2θ of 12° and 20° correspond to (020), (220), which showed that the chitosan had coated on copper oxide. The spectrum also shows the peaks in the range of 22.9°, 25.5°, 32.2°, 45.6°, 53.1°, 56.2°, 65.9°, 69.1°, and 77.4°, which correspond to the (021), (021), (110), (111), (020), (202), (− 113), (202) and (111) planes, respectively [18]. The XRD spectrum revealed that the prepared Chi-CuO nanocomposites had cubic crystalline structure, and the corresponding planes obtained were matched with the JCPDS File number (JCPDS NO: 05-0061) [18,19].…”
Section: Characterization Of Chi-cuo Nanocompositesmentioning
confidence: 94%
“…These approaches are vacuumbased deposition methods, which increase the cost and complexity of the process, and typically produce a mixture of copper oxide thin film and nanostructures. Methods such as electrochemical deposition [27,28] and sol-gel methods [29,30] can simplify the processing; yet they require hazardous or expensive solutions, respectively. Thermal oxidation methods [31,32] can provide a simple bottom-up approach of forming copper oxide nanostructures on a copper substrate.…”
Section: Introductionmentioning
confidence: 99%